HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN DI WILAYAH KERJA PUSKESMAS PEJERUK TAHUN 2022 - Satria, Alif Akira; Ningsih, Muthia (Aspiration of Health Journal, 2023)
Stunting is a state of a person's nutritional status based on a score of height (TB) for age (U) which is located at <-2 SD. The height/age index is an anthropometric index that describes nutritional conditions in the past and relates to environmental and socio-economic conditions. Stunting can interfere with intellectual growth and development. One way to prevent stunting is exclusive breastfeeding. Exclusive breastfeeding is giving breast milk (ASI) without adding and or replacing it with other food or drinks given to babies from birth for 6 months. However, there are still many mothers who do not give their toddlers exclusive breastfeeding. This study aims to determine the relationship between exclusive breastfeeding and stunting in infants aged 24-59 months in the working area of the Pejeruk Health Center in 2022. This type of research is an observational study with a cross-sectional research design. Sampling in this study used a purposive sampling technique, namely a sampling technique with certain considerations, with a total sample of 88 respondents. The results of the analysis of the relationship between exclusive breastfeeding and the incidence of stunting in toddlers 24-59 months in the Pejeruk Health Center Work Area in 2022 with a value (p value = 0.000) < α 0.05. Which shows that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-59 in the Pejeruk Health Center Work Area.